The Influence of Forefoot Bending Stiffness of Futsal Shoes on Multiple V-Cut Run Performance - Ismail, Shariman Ismadi; Nunome, Hiroyuki; Tamura, Yuji (Frontiers in Psychology, 2021)
Footwear’s forefoot bending stiffness property (FBS) is known to benefit athletes in running performance. To date, the efficacy of bending stiffness on performance is rather unknown from futsal shoes perspective. This study investigates the influence of bending stiffness property of three commercial futsal shoes on change of direction run resultant performance. Nineteen university level athletes participated the human performance test (multiple V-cut change of direction run) on a hardwood flooring facility using three pairs of futsal shoes (S1, S2 and S3) with different model but similar in outsole material (S1- mass: 311g; heel to toe drop: 10 mm; friction coefficient: 1.25, S2- mass: 232 g; heel to toe drop: 8 mm; friction coefficient: 1.34, and S3- mass: 276 g; heel to toe drop: 7 mm; friction coefficient: 1.30). The FBS properties for each shoe were mechanically measured. Results from analysis of variance indicated that there was significant difference of FBS value among the three shoes (S1: 0.32 Nm/deg., S2: 0.26 Nm/deg., and S3: 0.36 Nm/deg.) [F (2,8) = 28.50 (p<0.001)]. Shoes with relatively higher shoe–playing surface friction coefficient (S2 and S3) had significant impact on the V-cut performance (p<0.05) when compared to the shoe with lower friction coefficient (S1). In contrast to the literature, the shoe with the lowest FBS(S2) did not suffer any detriments on resultant performance in the test performed. These findings suggested that there could be other performance limiting factor such as the friction coefficient rather than FBS that have greater influence on the test outcome.